Corporate Social and Environmental Reporting in OHADA Context: Evidence from Companies Listed on the Douala Stock Exchange - Nganthou, Alexis; Boukar, Hamadou; Djeugou, Gaelle (Research Journal of Finance and Accounting, 2019)
This research questions the capacity of the OHADA accounting system to report on the societal commitment of companies. To carry out such a study, we are interested in the companies of the Douala Stock Exchange, which permanently publish green operations. The analysis was done at two levels: the first level of analysis highlighted the categories of green operations reported by the companies of our sample. The second level of analysis consisted in analysing the financial statements produced by these companies, in order to see in which accounts green transactions are recorded. The analysis reveals that, apart from some additional clarifications to be made in the appendices, the financial statements produced according to OHADA do not specifically highlight green information.
Keywords: Carry (investment); Green operations; Publication; Sample (material); Societal commitment; Stock (firearms)

Shareholder activism, corporate social responsibility and financial performance - Yang, Yi (Victoria University of Wellington, 2019)
The thesis examines the influence of shareholder activism on corporate social responsibility (CSR) disclosure of targeted firms and its spillover effects on CSR disclosure, corporate social performance (CSP) and financial performance (FP) respectively in peer firms. The research is motivated by filling the research gaps in prior literature and providing insights to shareholders, the management and regulatory bodies in practice. The thesis consists of three parts. Firstly, this thesis reviews the literature surrounding shareholder activism by conducting narrative reviews of 92 working papers and publications and meta-analysis on 55 working papers and publications, published during 2000-2017 period. Theories from prior literature, namely agency theory, stakeholder theory and stakeholder salience theory are analysed through narrative review analysis at the beginning of the chapter. Then, the analysis of narrative review also documents mixed findings of the associations among shareholder activism and FP and CG and CSP, including spillover effects. That is, the associations could be positive, negative and not significant in prior literature. The results of meta-analysis indicate that shareholder activism improves FP and CSP respectively. In addition, the thesis also examines the major types of shareholder activists and main forms of shareholder activism. Overall, through the analysis, the thesis identifies the research gaps of prior literature, thereby pointing out future research directions. Secondly, by employing shareholder proposals from Standard & Poor's 1,500 (S&P 1,500, hereafter) companies in the United States as a proxy of shareholder activism during 2006-2014 period with 13,572 separate observations, this thesis examines whether the whole sample of shareholder activism, institutional shareholder activism and coordinated shareholder activism could influence CSR disclosure level respectively. Simultaneously, this thesis also investigates whether shareholder activism affects CSR disclosure level given the other corporate governance mechanisms, namely board size, the presence of female directors, outside directors and CEO incentives. The results typically demonstrate that: (1) while shareholder activism negatively relates to CSR disclosure level, larger board size or the presence of female directors combined with shareholder activism directly relates to maintaining better CSR transparency; (2) coordinated shareholder activism could decrease social disclosure level. The findings also indicate that CSR disclosure provides an approach to strategically manage risks. Thirdly, the thesis explores spillover effects from different types of shareholder activism on CSR disclosure level, CSP and financial performance by using data gathered from S&P 1,500 companies during 2007-2014 period. The findings show that shareholder activism increases social disclosure level and environmental disclosure level in peer firms. It also shows that there is a weak positive association between shareholder activism and CSP. It therefore demonstrates the weak influences of shareholder activism in changing firms’ CSP. It also illustrates that institutional shareholder activism has an advantage over coordinated shareholder activism in terms of increasing corporate transparency. In this manner, it indicates that the collective action problem among coordinated shareholders could also attenuate the impact of shareholder activism in peer firms. The thesis contributes to the literature on shareholder activism practically and theoretically. The findings provide useful insights to shareholders, management teams and regulatory bodies for their policy-making. Beyond the practical contribution, the thesis also provides empirical evidence to stakeholder salience theory and analyses the collective action problem.
Keywords: CSR disclosure; Corporate Social Responsibility; Corporate governance; Corporate social performance; Financial performance; Shareholder activism

Assessing the nexus between corporate governance, corporate social responsibility and corporate regulation: the way forward for the OHADA zone - Tambutoh, Dashaco John; Tarh, Bande Gulbert Mbah (International Journal of Advanced Research and Publications, 2018)
Encyclopaedic Corporate Governance (CG) is now a mainstream issue of concern in the business world. Yet, there has been no systematic investigation of CG practices in general, allowing for a distinction between the profit and non-profit organizations. In this regard, this article aims to investigate the nuances in the application of sound governance principles across different types of organizations in general, together with the understanding and applications of Corporate Social Responsibility (CSR) and Corporate Regulation (CR) in the context of the OHADA zone. With CSR envisages as a model of CG that extends the fiduciary duties from fulfilment of responsibilities towards the shareholders of the firm to fulfilment of analogous fiduciary duties towards all the firm?s stakeholders. Thus, after considering the place of CSR in the debate about alternative CG modes, a full-fledged social contract foundation of the multi-stakeholder and multi-fiduciary model is present. The article, therefore, shows that CSR is a social norm that would endogenously emerge from the stakeholders? social contract seen as the first move in an equilibrium selection process that reaches the equilibrium state of a CG institution; and as a global trend involving corporations, states, international organizations and civil society organizations. Besides, the article portrays the trend of CSR in three ways: as a regulatory framework that places new demands on corporations; as a mobilization of corporate actors to assist the development aid of states and; as a management trend. With each of these portraits suggesting certain actors, relations, driving forces and interests as being central. These multiple identities may partially describe the trend?s success, but could equally well describe its contestation, fragility and fluidity. Based on the argument that CSR is not just a fashion but rather the future from another angle, the article explicitly explores the nexus between CSR, CG and CR as appreciated in the OHADA zone. It also presents fresh insights into the applications of CG and CSR principles under the OHADA perspective that has not received systematic attention and consideration in the literature and, thus, provides policy recommendations to mainstream a viable CSR framework in the OHADA zone.
Keywords: Corporate Regulation; Corporate Social Responsibility; Corporate governance; OHADA

The directors’ fiduciary duty to act in the best interests of the company: the possible developments of common law by statute and how they affect human rights - Nomadwayi, Bakhulule (University of KwaZulu-Natal, 2018)
This research traces the developments of the directors’ fiduciary duty to act in the best interests of the company and looks at how these developments affect human rights and interests of stakeholders. The main focus of the study is on the human rights impact of this duty. Initially, this duty was only regulated in terms of common law which proved to be problematic. The problem with common law lies within the definition of ‘best interests of the company’, which not only exclude the interests of other stakeholders but also has the potential to bring about violation of human rights, particularly the rights to equality, dignity and fair labour practice. At common law best interests of the company means interests of the company itself and its shareholders. The common law only protects the company and its shareholders, while excluding the rights and interests of stakeholders. The common law duty to in the best interests of the company is not in line with our contemporary law because it ignores human rights. The neglect of human rights by this duty renders it inconsistent with the values contained in the Constitution. Furthermore, the exclusion of stakeholders’ rights by this duty cannot be justified because stakeholders play an important part in safeguarding the stability and continued existence of the companies. The fiduciary duty to act in company’s best interests is now contained in the Companies Act of 2008. Inclusion of this duty in the Act enables our courts to interpret it in a manner that protects human rights and which takes into account interests of other stakeholders. Section 7 (a) of the Act provides that among other goals of the Act is the promotion of compliance with the Bill of Rights when applying the company law. The impact of section 7 is that it imposes an indirect duty on directors to consider the human rights impact of their decisions. Section 158 of the Act enables the courts to “develop common law as it is necessary to improve the realisation and enjoyment of rights established by the Companies Act of 2008.” Given this recognition of the Bill of Rights by the Companies Act, it’s of vital importance that our courts should interpret and apply the duty to act in the best interests of the company in manner that is consistent with the Constitution. Directors are now obliged to pay attention to the human rights impact of their decisions.
Keywords: Best interests of the company; CSR; Corporate Social Responsibility; Fiduciary duty

Trade, labour and sustainable development: an integrated perspective - Khan, Zobaida (McGill University, 2017)
Some contemporary challenges for global trade regulation and labour governance arise from the barriers between questions of law and social justice, and development policy and distributional issues. This thesis attempts to address some of these regulatory or governance challenges by exploring the interactions between sustainable development (SD), trade regulation, and social or distributive justice. Borrowing from multiple disciplines, i.e. law, international relations, and development economy, and focusing on the problems of low-income countries, this thesis examines the potential and importance of a broad ideational objective in introducing transformative changes in different regulatory or governance mechanisms. This thesis does not discuss ways to link trade regulation or labour governance with SD; rather here the possibilities of operationalizing SD, within the global trade regulatory site or transnational governance mechanisms, are explored from a capability perspective. It is argued that a capability-based understanding can resituate some questions on trade-SD interaction and introduce important behavioural changes in the functioning of the World Trade Organization (WTO). Yet, ongoing operationalization of capability-based SD requires effective market complementary interventions from governance mechanisms operating at different spaces and with diverse actors. Certain emerging transnational governance mechanisms, which connect broader social or distributional issues such as labour governance with trade opening or economic cooperation, attempt to provide crucial market complementary interventions. Taking examples from the recent transnational safety initiatives for Bangladeshi garment workers and relying on a broad conceptualization of the social or distributional issues, it is argued that attention to capability enhancement produces a much more compelling form of labour governance mechanism at these hybrid sites. With a focus on capability-based SD, a model of transformative linkage is proposed for effective labour governance. The model demands that fundamental and redistributive rights of labour are interconnected and appropriate labour governance requires a stronger form of corporate responsibility. Analyzing the interaction of diverse rules, governance processes and mechanisms, with the demands of marginalized forces the global hegemony of capital is juxtaposed with available options and possible alternatives.
Keywords: Corporate Social Responsibility; Labour; Social justice; Sustainable development; Trade regulation

The international legal framework on business and human rights and its domestic operationalisation : strategic litigation on mining and a healthy environment in South-Africa - Verdonck, Lieselot (Ghent University, 2017)
The debate on business and human rights attracts the interest of many parties, and regularly makes the headlines. On 19 January 2017 De Morgen, for instance, ran the following headline: “These banks do business with companies that violate human rights and nature”. The discourse suggests that few question that business enterprises should respect human rights. The legal meaning and consequences of associating 'business' with 'human rights' remain contentious, however. By clarifying the existing legal framework this thesis seeks to rationalize the debate. Special attention is paid to enforcing the responsibility of business enterprises for human rights through domestic judicial remedies. The analysis is concretised through a case study on adverse human rights impacts of environmental degradation caused by mining in South Africa. Based on the findings of the study, the thesis reflects on how the international legal framework on business and human rights should be developed further.
Keywords: Business; CSR; CSR disclosure; Human rights; International law; RSE; South Africa

CSR and financial performance parameters of DBBL: An empirical analysis - Farijul, Islam; Rahman, Mostafizur (International Journal of Innovation and Scientific Research, 2016)
The purpose of the current study is to show the statistical linkage between CSR expenditure of financial service firm mainly DBBL and its financial performance on the basis of some key parameters that attempts to contribute to the existing knowledge of corporate social responsibility initiatives by businesses and its ability to influence their financial performance. Consequently, the main objective is to examine the relationship between CSR and financial performance of the banking sector. For this purpose, various financial drivers are used such as EPS, DPS, NPAT, ROE, EVA ROA, MVA and, ROE and ROI. After getting all the relevant data from secondary sources like annual reports and reports from Bangladesh Bank, statistical tool like multivariate analysis in the form of Bi-variate Regression is used to depict the relationship and the developed hypotheses are tested by using Univariate analysis in the form of one sample t test under parametric test. The major finding of this study demonstrates evidence that there is a statistical significant linkage between CSR and Performance of the sample bank.
Keywords: CSR; DBBL; Financial performance parameters

Accountability of multinational corporations for human rights violations under international law - Mnyongani, Freddy (University of South Africa, 2016)
Jurisprudence
Keywords: CSR; Corporate Social Responsibility; Corporate governance; Human rights; International business enterprises; Liability for human rights violations; RSE; Social responsibility of business; Tort liability of corporations

Social legitimacy in the internal market : a dialogue of mutual responsiveness - Mulder, Jotte (European University Institute, 2016)
Social legitimacy is conventionally conceived to encompass an empirical notion based on the idea that, lacking societal acceptance, a (political or legal) regime will eventually disintegrate. This concern is reflected in the original compromise of 'embedded liberalism', which stands at the basis of the internal market of the European Union. The primary law set up of the internal market, indeed, shares the idea that the benefits of a joint commitment to free trade can only be achieved in a sustainable way if combined with an acknowledgement of domestic societal objectives within the same frameworks. Nevertheless, social legitimacy will eventually depend on the institutional design and structural rationales that embed societal values within such regimes and vice versa. This perspective is further developed, normatively, on the basis of the work of Karl Polanyi and adopted to critically assess the structural rationales that are developed within internal market adjudication, which the thesis approaches as a separate field of social ordering within the European Union. Thus, social legitimacy is developed as a requirement that perceives the legitimacy of internal market law on the basis of the extent to which it can respond and integrate social practice and values. On this point the thesis finds that the internal market lacks a sufficiently developed rationale or "common language" that is able to address the normative concerns of social legitimacy. Societal realities are often valued within a metric that risks doing violence to potentially genuine and worthwhile aspects of Member States' 'social spheres'. The thesis develops that the normative claims of social legitimacy are best addressed on the basis of a rationale of mutual responsiveness, which is considered a necessary but underdeveloped element of the constitutional form and social purpose of the internal market that is implicit in the constitutional theory of transnational effects. From a perspective of mutual responsiveness, the social purpose of the internal market is not to condition choices that necessarily require the market to trump the social sphere - or the opposite- to allow the social to necessarily trump the market. Mutual responsiveness advances a more holistic approach that conceives the market and the social, literally, as 'communicating vessels'. The normative concerns of social legitimacy and the potential of mutual responsiveness to address these normative claims are the central and connecting elements throughout the thesis.
Keywords: Commercial law; European Union countries; Free Trade; Trade regulation

Corporate Social Responsibility , Oil Exploration and the Niger Delta Question - Obi, Emeka Anthony (Oman Chapter of Arabian Journal of Business and Management Review, 2015)
The intricate relationship between corporate organizations and their environment is one that is supposed to be based on mutual interdependence. This is because the organization depends on the environment for its inputs, while the environment also needs the organization for its sustenance. This therefore calls for a symbiotic relationship between them. It is this realization that gave birth to the concept of Corporate Social Responsibility (CSR). This paper tries to look at the application of the concept as it concerns the oil companies operating in the Niger Delta region of Nigeria within the ambit of the Niger Delta question. The study employs the systems theory as an analytical framework. It tries to situate the concept of CSR within the general neglect by successive governments of this region that sustains the entire Nigerian state. The implication of the above is that a better understanding of the problem of CSR in the Niger Delta region becomes easier when juxtaposed with the attitude of the Nigerian state towards the region over the years. It is the summation of the paper that the oil companies have not been very proactive in this regard and as such have been perceived by their host communities as enemies and exploiters instead of partners. The study concludes by insisting that while the oil companies should be more proactive, the government on her part should step up the tempo in ameliorating the deplorable condition of the golden goose.
Keywords: CSR; Corporate Social Responsibility; RSE; Responsabilité Sociale de l'Entreprise

Labour rights and working conditions in corporate codes of conduct: an assessment of the legal dimension, in different national contexts, of selected multinational corporations’ corporate social responsibility commitments - Tiemeni, Thierry Galani (University of the Western Cape, 2015)
At the heart of this thesis is the notion of Corporate Social Responsibility (CSR), an innovative concept deep-rooted in the globalisation phenomenon. The notion of CSR entails the much-debated duty of businesses, not only to comply with international and local standards in terms of, inter alia, labour rights and working conditions, human rights and environmental protection, but also to be at the forefront of voluntary and uplifting actions geared toward addressing societal issues and concerns. For corporations, it is about moving from the traditional approach of business as an activity with the sole purpose of realising profit towards acknowledging the need to integrate societal and environmental issues and concerns into their business purposes. The thesis examines selected multinational corporations’ (MNC) approaches to CSR as contained in their codes of conduct, in an effort to reach a comprehensive understanding of the purpose, interest and practices of businesses engaging in CSR activities. Particular attention is given to the analysis of labour orientated measures implemented by selected MNCs as they undertake to voluntarily act as proponents of the theory of the necessity of socially responsible businesses. The aim is to comparatively assess the legal dimension and the relevance, in different countries, of these MNC CSR commitments. The first part of the thesis is theoretical and has the purpose to present a comprehensive analysis of CSR against the current legal framework, at a global scale and within the context of selected countries. The thesis will explore the notion of CSR in order to present its definition and characteristics, briefly retrace its history, differentiate it from related and/or similar concepts, and finally assess the extent of its introduction and adaptation into various national and international institutional frameworks. Even though initially addressing the issue of CSR in the current legal framework as a whole, the scope of the thesis will ultimately be reduced to focus only on labour-related aspects of CSR. The aim of the thesis is to assess MNC’s CSR commitments, and subsequently highlight the interaction between CSR, labour and employment legal frameworks (at national and international level) and the effective implementation of labour rights and working conditions as observed in the context of different countries. More importantly, the thesis will also include a comparative analysis of CSR principles included in selected MNC codes of conduct, in order to assess the extent of their compliance with national labour legislation, international labour standards, as well as the standards and principles set by national and international CSR instruments and institutions. The purpose of such an exercise is to thoroughly assess the impact of a national context - in terms of national legal, economic, social and industrial framework - on the legal dimension, and the relevance of MNCs CSR commitments. A crucial argument developed in the thesis refers to the fact that MNC codes of conduct may have the potential to impact on labour rights and working conditions of a MNC across the different countries into which the MNC operates. Finally, considering the fact that as a topic CSR is a potentially controversial subject, it is necessary to point out, from the onset, that the thesis engages with the subject from a critical perspective. The approach therefore entails critically analysing and discussing MNC commitments and practices as observed in different countries, so as to be able to ascertain and comprehend the impact of a national context on the content, the relevance and the legal dimension of MNC codes of conducts
Keywords: Code of conduct; Corporate Social Responsibility; Labour rights; Multinational corporations; Working conditions

The primary importance of corporate social responsibility and ethicality in corporation reputation: an empirical study - Walker, Kent; Dyck, Bruno (Business and Society Review, 2014)
We examine three assumptions commonly held in the corporate reputation literature: i) reputation ratings of owners and investors are generally representative of all stakeholders; ii) stakeholders will generally provide a higher reputation rating to firms that emphasize corporate social responsibility versus firms that do not; and iii) profitability is the primary criterion of importance to all stakeholders when rating a firm’s reputation. Using an exploratory in-class exercise our findings suggest that: i) there are significant differences among stakeholder groups in their reputation ratings; ii) firms that emphasize corporate social responsibility are not rated more highly across all stakeholder groups, and iii) for all stakeholder groups, the ethicality criterion explained more of the variance in firms’ reputation ratings than the profitability criterion.
Keywords: CSR; Corporate Reputation; Corporate Social Responsibility; Criteria; Ethics; Profitability; RSE; Stakeholders

Corporate Social Responsibility (CSR) in the OHADA Law - Diawara, Karounga; Lavallée, Sophie (Journal of Business Law and Ethics, 2014)
CSR refers primarily to a framework idea according to which a corporation is encouraged, if not obliged, to go beyond the speculative and economic goals that benefit its members only, in order to integrate, into its decision-making process, other more holistic considerations of an ethical, social and environmental nature for the benefit of all stakeholders. CSR is a key concept that attempts to reconcile economic objectives with social, ethical and environmental considerations, with the particularity of questioning interactions between a corporation and its societal, ethical and ecological environment. This paper has a modest, but not uninteresting, objective. First, it offers an exploratory study that sets out markers for a more exhaustive analysis of the potential for CSR in the field of law in the Ohada zone. Our study is intended to be both theoretical and pragmatic: it asks questions and suggests topics for review from a normative standpoint largely inspired by socio-economic analysis. One of the interesting features of our approach is to consider, comprehensively, a complex notion that reflects several different concerns and is crossed by various conceptual frameworks that must be re-read in an “enlightened” manner, to see how it could potentially be made operational as part of Ohada law. This previously unexplored approach could lead, in time, to the establishment of a transnational committee on CSR in the Ohada zone.
Keywords: CSR; RSE

Nigeria, oil and gas exploration and the Niger delta question : a study in corporate social responsibility - Bribena, E. K. (North-West University, 2011)
This thesis addresses issues of the Niger Delta question which represents one of the most intractable sources of socio-political destabilization in the Niger Delta region of Nigeria. The study is on the intricate dynamics amongst the Nigerian state, the transnational oi l corporations, the oil producing communities and the insurgent militia conflict. It investigates and explicates the "paradox of plenty" and the "resource curse", the "absentee government" and "state capture" and the debilitating effects of petroleum politics in Nigeria. The economic exploitation of the Niger Delta region's vast crude oil reserves by transnational oil corporations and government authorities is juxtaposed with the spectre of environmental degradation, human rights violations, and the recurrent rule of impunity. The protracted problems of the Niger Delta region thus, provide us with a pertinent analytical and contextual framework for the study of the dynamics and issues of transparency in other African petro-dollar states. It is argued in this study that the Niger Delta crisis is a conflict of values and fight for resources arising from decades of unacceptable standards of oil exploration and the absentee character of the Nigerian State. By its very nature, the study called for a qualitative approach, supplemented by unstructured interviews using aide memoirs with selected officials, on the basis of their innate knowledge of the subject matter. The legal comparative research method, with a historic component also played an integral role in this study. Some key findings and conclusions: 1. The study found that the Niger Delta crisis graduated from mère political agitations for state creation and provision of social amenities to extreme acts of hostage-taking and a twist of violence as a result of treating a major problem affecting the development of the Niger Delta people with levity for too long a period. 2. The study found that the on-going crisis in the Niger Delta region of Nigeria is a conflict of values and fight for resources amongst the oil-bearing people of the Niger Delta, transnational oil corporations and the Nigerian Government. 3. The study established some causal nexus between oil and poverty; oil and corruption; and, oil and human rights abuses. 4. That, the Niger Delta crude oil conflict is essentially a manifestation of state capture and inertia on the part of the Nigerian Government. 5. The study found that the Niger Delta economies are "criminalized" and are often characterized by conditions of anarchy and impunity. And this disorder is embedded in the dynamics of resource extraction, the nature and role of "shadow" state actors, as well as the interplay and patterns of relationships between organized criminal syndicates and the transnational oil corporations in the host communities. The study recommends, inter alia: I. That steps be taken by government to re-define its philosophy of national economic development from a state-driven to citizens-driven philosophy. To this end, Nigeria must seek to develop by developing its citizens, the aggregate of whose satisfactory living conditions should form the criteria for measuring national development. II . That effort must be made to steer the nation towards proper fiscal federalism. The present "food is ready" economy whereby federating units are enslaved to national "cake sharing" instead of value generation, discourages entrepreneurship and sustainable development. It promotes undue dependency on petroleum products, inequity and ethnic distrust. Ill. That Nigeria needs productive resource control, not just development in the sense of house and bridge building. What is needed is a noticeable leap in the standard of living in the Niger Delta. Thus, people and not federal accounts must be the object of improvement. IV. It is recommended that government should ensure robust, independent and co-ordinated oversight of the oil industry including its impact on human rights. V. Transnational oil corporations should undertake full corporate social responsibility and comprehensive assessment of the social and human rights impacts of all oil and gas projects, ensuring that adequate information is provided to affected individuals and communities and that the process is transparent. VI. It is strongly recommended that an Oil Pollution Liability Trust Fund should be established by the Federal Government in concert with oil companies. The fund will be made up of a percentage of tax levied on oil companies and a percentage of earnings of the Federal Government from oil. The fund should be used in ameliorating the conditions of the impacted environment and people. It is hoped that these findings and recommendations will go a long way in the quest for significant environmental and social improvements in the Niger Delta region of Nigeria.
Keywords: CSR; Corporate Social Responsibility; Nigeria; Petroleum industry and trade

Exploring the limits of Western Corporate Social Responsibility Theories in Africa - Dartey-Baah, Kwasi; Amponsah-Tawiah, Kwesi (International Journal of Business and Social Science, 2011)
Corporate Social Responsibility (CSR) is about the relationship of organisations with society as a whole, and the need for organisations to align their values with societal expectations. Generally, CSR practice in Africa is thought to be adopted from Western business theories although there is evidence to suggest that Western CSR theories are not totally applicable in Africa. This is due to differences in drivers or causes of CSR in the West and in Africa, as well as cultural and managerial traits in Africa. This paper explores the limits of Western CSR Theories in Africa and argues that improved ethical responsibilities, incorporating good governance should be assigned the highest CSR priority in developing countries. It further adds that increased legislation, change in CSR priorities and the application of indigenous CSR theories such as Ubuntu, African Renaissance and Omuluwabi are means of countering the limits of Western CSR theories in Africa. Keywords: CSR, Western CSR Theory, Africa, Ubuntu, African Renaissance, Omuluwabi
Keywords: Africa; CSR; RSE; Renaissance; Ubuntu; Western CSR Theory